Pemberdayaan Ketahanan Pangan pada Stunting di Desa Buana Mekar Kecamatan Panumbangan Kabupaten Ciamis - Elis Roslianti; Siti Rahmah Kurnia Ramdan; Anna L Yusuf; Ade Raina (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: Stunting is a condition where a child experiences growth disorders, so that the child's height and weight do not match his age. This is caused by a lack of nutritional intake for a long time. Indonesia is a country with multiple nutritional problems, characterized by a high prevalence of stunting and anemia in pregnant women. Objective: The aim here is that it is hoped that stunting cases that exist, especially in the Buana Mekar Village area, can be prevented. In this way, children can grow and develop well so that an intelligent and healthy young generation is created. Method: The community service method is carried out through counseling and discussions with female cadres at the Buana Mekar Village Hall, Ciamis Regency. Result: Based on counseling activities, it can be concluded that 16 people (40%) of the participants were able to answer questions before the implementation of health education, before the material was delivered, there were 24 people (60%) who did not answer questions. And after the presentation was delivered, the participants' knowledge increased 100%. So it can be concluded that the participants present quite understand the material presented. Conclusion: The conclusion of the implementation of health counseling activities regarding the handling of stunting went well in accordance with what was expected and planned. This health education is effective and has positive values for the counseling participants. This can be seen from the enthusiasm and activeness of these health education participants and the increasing knowledge about handling resistance to stunting before and after education is given.